De novo transcriptome analysis of high-salinity stress-induced antioxidant activity and plant phytohormone alterations in Sesuvium portulacastrum - Chen, YiQing; Zhou, Yan; Cai, Yuyi; Feng, Yongpei; Zhong, Cairong; Fang, ZanShan; Zhang, Ying (Frontiers in Plant Science, 2022)
Sesuvium portulacastrum has a strong salt tolerance and can grow in saline and alkaline coastal and inland habitats. This study investigated the physiological and molecular responses of S. portulacastrum to high salinity by analyzing changes in plant phytohormones and antioxidant activity, including their differentially expressed genes (DEGs) under similar high salinity conditions. High salinity significantly affected proline (Pro) and hydrogen peroxide in S. portulacastrum seedlings, increasing Pro and H2O2 content by 290.56% and 83.36%, respectively, compared to the control. Antioxidant activities, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) significantly increased by 83.05%, 205.14%, and 751.87%, respectively, under high salinity. Meanwhile, abscisic acid (ABA) and gibberellic acid (GA3) contents showed the reverse trend of high salt treatment. De novo transcriptome analysis showed that 36,676 unigenes were matched, and 3,622 salt-stress-induced DEGs were identified as being associated with the metabolic and biological regulation processes of antioxidant activity and plant phytohormones. PODs and SOD were up-regulated under high-salinity conditions. In addition, the transcription levels of genes involved in auxin (SAURs and GH3), ethylene (ERF1, ERF3, ERF114, and ABR1), ABA (PP2C), and GA3 (PIF3) transport or signaling were altered. This study identified key metabolic and biological processes and putative genes involved in the high salt tolerance of S. portulacastrum and is of great significance for identifying new salt-tolerant genes to promote ecological restoration of the coastal strand.